Changes over 5 years in utilization of dental care by a Swedish age cohort - Sta°hlnacke K, So¨derfeldt B, Unell L, Halling A, Axtelius B. (Blackwell Synergy, 2005)
The purpose of this study was to investigate the temporal development of the utilization of dental care, in relation to socio-economic factors and also considering perceived oral health, attitudes to dental care, dental anxiety, care organisation and changes in the way that dental care is paid for.